Penegakkan Hukum serta Upaya Penyelesaian Sengketa Online Marketplace melalui Mekanisme Online Dispute Resolution - Lusiona Mas Sagala; Devi Siti Hamzah Marpaung (Universitas Widya Gama Malang, 2021)
The purpose of this study is to determine the regulation of online buying and selling transactions in the Marketplace and consumer disputes that occur in the Marketplace as well as efforts to resolve consumer disputes through the Online Dispute Resolution Mechanism. This study uses a normative juridical method with two types of legal materials, namely primary legal materials and secondary legal materials. Content analysis is used as a form of technique in analysis so that it does not require data in the field. Through this research, it can be seen that the regulation of online buying and selling transactions in the Marketplace is similar to direct or conventional transactions. Even though there is already a policy regarding online transactions, it cannot completely avoid consumer disputes. Therefore, online settlement efforts are needed, namely through Online Dispute Resolution (ODR) with the negotiation, mediation, and arbitration methods.